A Boutique Hotel’s Journey into Turning ‘Green’: A Case Study of Atanaya Hotel Bali - Irene Emmanuelawati (International Journal of Glocal Tourism, 2021)
Abstract: Purpose: This article is a case study which aimed to briefly evaluate the journey of Atanaya hotel towards green predicate; how they operate on a daily basis to emulate green lifestyle and to minimize their unfavorable business impacts on natural environment. Research methods: This study was performed in a qualitative approach, in which the data collection was summarized through a case study in the form of on-the-spot field research and questionnaires, followed by interviews with the General Manager as well as the Owner of Atanaya Hotel Bali. Findings: Common rooms are airy and surrounded by plantations, while guest rooms have also already been supplied with eco-friendly appliances. The hotel has carried out this type of management since 2018. Overall, considerable efforts have been put by Atanaya Hotel Bali into adapting environmentally-friendly concepts, although the hotel itself has not publicly announced its green hotel policy. Implication: Atanaya Hotel Bali successfully followed the protocol towards being accredited as a sustainable, ecological hotel while maintaining their rates at competitive level.